2018
DOI: 10.1002/2017gb005790
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Budget of Tidal Wetlands, Estuaries, and Shelf Waters of Eastern North America

Abstract: Carbon cycling in the coastal zone affects global carbon budgets and is critical for understanding the urgent issues of hypoxia, acidification, and tidal wetland loss. However, there are no regional carbon budgets spanning the three main ecosystems in coastal waters: tidal wetlands, estuaries, and shelf waters. Here we construct such a budget for eastern North America using historical data, empirical models, remote sensing algorithms, and process‐based models. Considering the net fluxes of total carbon at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
155
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 151 publications
(276 reference statements)
8
155
2
Order By: Relevance
“…A recent modeling analysis based on a 30‐year time period also concluded that the CB main stem is net autotrophic (Shen, Testa, Ni, et al, ; Shen, Testa, Li, ). Finally, both Najjar et al () and Herrmann et al () classified the CB as net autotrophic, despite their conclusion that the majority of estuarine systems on the east coast of the United States are heterotrophic. The results of this study, however, indicate that the whole water column of the CB mainstem during the 2016/2017 study period is net heterotrophic, suggesting the region may behave more similarly to other east coast estuaries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent modeling analysis based on a 30‐year time period also concluded that the CB main stem is net autotrophic (Shen, Testa, Ni, et al, ; Shen, Testa, Li, ). Finally, both Najjar et al () and Herrmann et al () classified the CB as net autotrophic, despite their conclusion that the majority of estuarine systems on the east coast of the United States are heterotrophic. The results of this study, however, indicate that the whole water column of the CB mainstem during the 2016/2017 study period is net heterotrophic, suggesting the region may behave more similarly to other east coast estuaries.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike the CB, the Delaware Bay does not experience the impacts of eutrophication due to a lack of seasonal stratification (Sharp et al, ); the phytoplankton growth that is initiated after the introduction of excess nutrients to the upper CB contributes to maintaining p CO 2 undersaturation and the sink for atmospheric CO 2 . More broadly, Najjar et al () showed that outgassing generally increases from Gulf of Maine estuaries (35 ± 9‐g C m −2 ·year −1 ) to mid‐Atlantic Bight estuaries (52 ± 46 g C m −2 ·year −1 ) to South Atlantic Bight estuaries (246 ± 117 g C m −2 ·year −1 ). Our results indicate that CB uptake of atmospheric CO 2 (4.5 ± 1.2 g C m −2 ·year −1 ) is an exception to this latitudinal gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding impacts of increasing p CO 2 , climate change (precipitation and temperature), and land use change (supply of nutrients and carbon) on estuarine carbon budgets is critical for improving estimates of estuarine carbon exchange with the ocean and atmosphere. Most previous estuarine metabolism and CO 2 studies indicate that estuaries are generally net heterotrophic (Najjar et al, ; Smith & Hollibaugh, ), respiring more organic carbon than they produce, resulting in an overall mean global estuarine CO 2 degassing flux of 26 mmol·m −2 ·year −1 (Borges & Abril, ). However, some larger, marine‐influenced estuaries (Kemp et al, ) and small, benthic‐dominated tropical estuaries (Kone et al, ; Maher & Eyre, ) have been shown to be net autotrophic, revealing the diversity of metabolic states in estuarine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Windham‐Myers et al () found tidal wetland burial to be about 6 times estuarine burial, but our results suggest that tidal wetland burial is only about 50% greater than estuarine burial. Regarding U.S. East Coast waters as a whole, Najjar et al () found estuaries to account for 20 ± 9% of the total burial of 2.5 ± 0.7 Tg OC/yr, with the remainder roughly evenly split between tidal wetlands and shelf waters. In contrast, our results suggest total burial to be 4.1 ± 1.2 Tg OC/yr, with estuaries making up the largest contribution (51 ± 29).…”
Section: Resultsmentioning
confidence: 99%